Probing nanoscale structure and strain by dark-field x-ray microscopy. (April 2020) - Yildirim, Can; Cook, Phil; Detlefs, Carsten; Simons, Hugh; Poulsen, Henning Friis
Abstract: Abstract : Dark-field x-ray microscopy is intended for the acquisition of three -dimensional (3D) movies of the nanostructure (grains, domains, and dislocations) and the associated local strain within bulk materials. It is analogous to dark-field electron microscopy in that an objective lens magnifies diffracting features of the sample. The use of high-energy synchrotron x-rays, however, means that these microstructural features can be large and deeply embedded. The spatial and angular resolution is on the order of 100 nm and 0.001°, respectively, and full maps can be recorded in seconds to minutes. Four applications of the technique are presented—domain switching in ferroelectrics, processing of metals, microstructural characterization of biominerals, and visualization of dislocations. The ability to directly characterize complex, multiscale phenomena in situ —and in 3D—is a key step toward formulating and validating multiscale models that account for the entire heterogeneity of materials.